SUSTAINABLE CONSTRUCTION AND DEMOLITION WASTE MANAGEMENT IN MALAYSIA: CURRENT ISSUES (Jurnal Kemanusiaan, 2017)
ABSTRACT Construction and Demolition Waste (CDW) is a deep concern for most developing countries with a harmful impact on the environment, society, and economy. This study attempts to offer insights into the management practices of CDW and to identify several barriers that hinder the future management of CDW in Malaysia. The data collection approach includes a thorough review of all CDW related academic papers, official reports and statistics, and government legislations. This study also includes the issues and challenges of sustainable management of CDW in Malaysia with the aim of demonstrating the current challenges related to sustainability of CDW. The findings of this study will contribute substantial evidences to both academicians and practitioners towards better management and planning of policies for CDW.